(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The emergence of the knowledge based society is changing the global status of education. It is the time to develop a new knowledge based global society. This is an age knowledge exploration and explosion. Many innovations like e-lectures, collaborative learning and teaching, tele-teaching, student self-assessment through automated interactive online testing, use of digital resource libraries and the interact and world wide web are the educational tools and techniques of the future. It is the right time for the teacher educators to use more varied and effective teaching learning strategies with employing the most advanced electronic devices which can access and process the rapid knowledge explosion.